Pengaruh Nilai Rukar Rupiah, Suku Bunga Indonesia Dan Inflasi Terhadap Return Saham Dengan Profitabilitas Sebagai Variabel Intervening Pada Perusahaan Perbankan di Bursa Efek Indonesia (BEI) Tahun 2012-2015 - Galih Gerranda Ramadhani (Program Studi Manajemen Fakultas Ekonomi UST, 2018)
The purpose of this study is to describe (1) To analyze and understand the effect of exchange rate on stock returns, (2) To analyze and understand the effect of Inflation on stock return, (3) To analyze and understand the effect of SBI on stock return, (4) To analyze and understand the effect of exchange rate on profitability, (5) To analyze and understand the effect of Inflation on profitability, (6) To analyze and understand the effect of SBI on profitability, (7) To analyze and understand the effect of profitability on stock return (8) the influence of Exchange Rate, Inflation, and SBI simultaneously affect the profitability, (9) To determine the effect of Exchange Rate, Inflation, and SBI simultaneously affect the stock return. The population in this research is BUMN and Private Bank in Indonesia which amounts to 41 companies and the samples of 8 companies. Data collection method is secondary data, while data analysis technique use multiple regression analysis supported by F test and T test and classical assumption test consist of normality test, multicolinearity test, heterokedasitas test, autocorrelation test. The results showed that multiple linear regression equations for three predictors are ROA = 2,913 + 0,0003642Kurs- 20,709Suku Bunga - 1,372Inflasi + e .... (1) means the exchange rate (X1), interest rate (X2), and inflation (X3) not great on profitability. Can be seen from the coefficient of determination (R2) 7.2%. This means that independent variables have a positive effect on profitability of 7.2% and the remaining 92.8% influenced by other variables. And the results of other studies show that multiple linear regression equations for four predictors are Return = 0.042 + 0.0001587kurs - 2.547suku bunga - 0.549inflasi-0,006ROA + e ...... (2) means Exchange rate (X1), interest rate (X2), inflation ( X3) and profitability (X4) contributed substantially to stock returns. Can be seen from the coefficient of determination (R2) 0.11. This means independent variables have a positive effect on profitability of 11% and the remaining 89% influenced by other variables.